THE FAMILY AND ITS CONFIGURATION STARTING FROM THE FORCED DISPLACEMENT - Gómez Builes, Gloria Marcela (Investigación y Educación en Enfermería, 2008)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> The families who have arrived to Medellín under a situation of displacement forced by the violence, constitutes a human group which expresses particular characteristics and needs. Objective: to describe life conditions of the population in forced situation displacement settled in “El palomar”, in the district “Bello Oriente” of Medellín between May of 2004-December of 2005, and the changes in the family before and after the displacement. Methodology: The present study was made from a qualitative approach, under the view of focused ethnography. Results: they stand out the process of transformation in the family, according to their dynamic and structures, specifying the changes based on rolls, functions, contexts, possibilities and limitations which occur from the forced displacement itself. Conclusion: the situation of displacement implies families interaction, with the urban world, being other people to their customs and forms to understand the world, prevails and some possible conditions of development and accomplishment of the families and their members, increases vulnerability situation and social and economic exclusion, taking shape in the violation of the right to the family.